Social determinants of health pave the path to maternal deaths in rural Sri Lanka: reflections from social autopsies - Lasandha Irangani; Indika Ruwan Prasanna; Sajaan Praveena Gunarathne; Sandaru Hasaranga Shanthapriya; Nuwan Darshana Wickramasinghe; Suneth Buddhika Agampodi; Thilini Chanchala Agampodi (BMC, 2022)
Plain English summary Many women in low and middle-income countries die during pregnancy, childbirth, or postpartum due to preventable factors. Routine inquiries into these deaths conducted by health personnel focus mainly on problems in health systems, neglecting social causes. We explored how social factors paved the path to maternal deaths inquiring the immediate community. We conducted 43 interviews with close persons and observations of 15/18 deceased women within 2 consecutive years, in district A (pseudonymized) in Sri Lanka. We included all deaths that occurred in the hospital as well as the field during the study period. The patterns of social causes based on the type of maternal deaths were analyzed using mixed methods. Extreme poverty, low educational level, gender inequity, and elementary or below-level occupations of the husband were common in most deceased families. Social isolation was the commonest leading cause and resulted in poor social support making women helpless. We observe that poverty, social isolation, and poor social support at family and neighborhood level acted together with alcohol usage and violence, leading to suicides and to delay in health-seeking. Deficits in quality of health care and negligence were noted in hospitals and in field care provision. We conclude that it is of prime importance to identify social causes leading to deaths of women during pregnancy and postpartum, as prevention of these is possible through simple multisectoral interventions. The health system needs to be integrated with social interventions and systems at community level to identify women at risk.